Development of an Instrument for Assessing Critical Thinking in Science Learning among Secondary School Students: A Systematic Literature Review - Salma Hafizhati Millatina Azka; Wiwi Isnaeni; Djuniadi Djuniadi; Prasetyo Listiaji (UIN Fatmawati Sukarno Bengkulu, 2026)
This systematic review synthesizes recent studies on the development and validation of critical thinking assessment instruments in science learning among secondary school students published between 2015 and 2025. Using the PRISMA 2020 framework, 20 eligible articles were identified from Scopus, Web of Science, and Crossref. The findings showed that reasoned multiple-choice test and essay tests were the most widely used formats, with Facione, Ennis, and the revised Bloom’s taxonomy serving as the dominant theoretical frameworks. Most instruments demonstrated good content validity and reliability, although evidence for construct validity remains limited. Instruments were primarily developed for senior high school students, focusing on biology, chemistry, and physics contexts, while development of instrument at the junior high school level were relatively scarce. Several studies also incorporated additional variables related to critical thinking, including science process skills, creative thinking, self-efficacy, and scientific literacy. Identified research gaps include the limited use of performance-based assessments, insufficient construct validity testing, and a lack of contextually grounded frameworks. These gaps highlight the need for more authentic, multidimensional, and empirically robust assessment models to measure students’ critical thinking skills in science learning.